The European Central Bank and EU procurement law: A comparative outlook - Fabian von Lindeiner; Giuseppe Bitti; Michelle Hermans (European Central Bank (ECB), 2019)
Procurement law is rising in importance year after year. According to the European Commission, public procurement now accounts for over 14% of the EU's gross domestic product. Also at the ECB, spending through procurement is growing, and the evolution of its procurement law from non- binding internal guidelines to a transparent and comprehensive legal framework is a clear reflection of this development. The purpose of this working paper is to summarise the legal framework for public procurement at the ECB, to compare it to the procurement rules of other EU institutions, and to analyse four key issues in contract award procedures, with due regard to the EU procurement directives and the case law of the Court of Justice of the EU. Due to its specific legal status and organisational autonomy, the ECB can define and adopt its own procurement rules. It is not subject to the EU procurement directiv es. They are addressed to Member States and not to EU institutions. The ECB is also not bound by the EU Financial Regulation, which applies to most other EU institutions financed from the EU budget. The working paper starts with a look back on the evolutio n of the ECB's procurement rules since the establishment of the bank in 1998. We then analyse the current framework, laid down in Decision ECB/2016/2, in more detail. The second chapter summarises public procurement rules of other EU institutions, namely, the Financial Regulation and the procurement guide of the European Investment Bank which, like the ECB, is not subject to the Financial Regulation. The third chapter analyses how the differences in these legal frameworks affect procurement procedures in pr actice, with a focus on four key aspects of the award process: selection and award criteria, transparency and publication, proportionality and legal remedies. The working paper concludes with a comparative summary of the current state of public procurement law at the EU institutions
Keywords: K23; K40; 330; European Central Bank; Public Procurement; European Investment Bank; Financial Regulation; EU Procurement Directives; selection and award criteria; proportionality principle; transparency principle; legal remedies